Case reportAbsence of superficial palmar arch with associated anomaly of ulnar artery and nerve: a case report with clinical implications - Paul, Shipra; Das, Srijit (Archives of Medical Science, 2007)
Normally the ulnar artery and the ulnar nerve pass superficial to the flexor retinaculum of the wrist. In the present study, we describe an ulnar artery and ulnar nerve which passed deep to the flexor retinaculum and an absent superficial palmar arch. Abnormal course of ulnar nerve and ulnar artery passing deep to the flexor retinaculum with absence of a characteristic superficial palmar arch is a rare finding. The ulnar vessels and nerves when passing deep to the flexor retinaculum are vulnerable to compression and may be important for clinicians diagnosing compressive neuropathies and surgeons operating on the wrist.